Studi Literatur Pemanfaatan Teknologi Pada Proses Pengajaran Kurikulum Merdeka (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This research uses the literature study method to examine the use of technology in the Independent Curriculum teaching process. Where, data collection is carried out by reading and recording various literature relevant to the title of this article, the research is carried out in a non-interactive and sustainable manner. The Merdeka Curriculum requires teachers to be literate in technology and students can master numeracy and technological literacy. With various variations of technology, many innovations are generated in technology for teaching, one example is the use of digital comics as one of the learning media, which aims to prevent students from feeling bored with all the written texts explained by the teacher. Based on the results of previous research, the technology used as teaching in this independent curriculum has not been conveyed evenly enough to teachers, because there are still many teachers who are not proficient in utilizing technology, so that teachers must understand the independent curriculum themselves in order to achieve the competencies expected in the vision and mission of the independent curriculum.